Natural Alkaloids Intervening the Insulin Pathway: New Hopes for Anti-Diabetic Agents? - Christodoulou, Maria-Ioanna; Tchoumtchoua, Job; Skaltsounis, Alexios-Leandros; Scorilas, Andreas; Halabalaki, Maria (Current Medicinal Chemistry, 2019)
Background: Accumulating experimental data supports the capacity of natural compounds to intervene in complicated molecular pathways underlying the pathogenesis of certain human morbidities. Among them, diabetes is now a world’s epidemic associated with increased risk of death; thus, the detection of novel anti-diabetic agents and/or adjuvants is of vital importance. Alkaloids represent a diverse group of natural products with a range of therapeutic properties; during the last 20 years, published research on their anti-diabetic capacity has been tremendously increased. Purpose: To discuss current concepts on the anti-diabetic impact of certain alkaloids, with special reference to their molecular targets throughout the insulin-signaling pathway. Methodology: Upon in-depth search in the SCOPUS and PUBMED databases, the literature on alkaloids with insulin secretion/sensitization properties was critically reviewed. Results: In-vitro and in-vivo evidence supports the effect of berberine, trigonelline, piperine, oxymatrine, vindoneline, evodiamine and neferine on insulin-signaling and related cascades in beta-cells, myocytes, adipocytes, hepatocytes and other cells. Associated receptors, kinases, hormones and cytokines, are affected in terms of gene transcription, protein expression, activity and/or phosphorylation. Pathophysiological processes associated with insulin resistance, beta-cell failure, oxidative stress and inflammation, as well as clinical phenotype are also influenced. Discussion: Growing evidence suggests the ability of specific alkaloids to intervene in the insulin-signal transduction pathway, reverse molecular defects resulting in insulin resistance and glucose intolerance and improve disease complications, in-vitro and in-vivo. Future indepth molecular studies are expected to elucidate their exact mechanism of action, while large clinical trials are urgently needed to assess their potential as anti-diabetic agents.
Keywords: diabetes mellitus (DM)